PESTICIDE HANDLING AND ASSOCIATED HEALTH RISKS AMONG AGROCHEMICAL RETAILERS IN OSUN STATE, NIGERIA - SOSAN, MOSUDI B.; ONI , OLUFUNMILAYO; FOLORUNSO, DAYO O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This paper assessed the knowledge, attitude and practice (UP) of agrochemical retailers with respect to pesticides handling and practices that might potentially expose them to chemical hazards in Osun State, Nigeria. Using a purposive sampling procedure, structured questionnaire was used to collect quantitative information from selected agrochemical retailers and this was supplemented with oral interviews. Information collected included the respondents' background, training and experience in agrochemical trade, their perceived awareness on the hazardous nature of products they sell and health complaints and symptoms of exposure experienced. Results show that majority (71%) of the respondents were in the age range of 20-39 years. Pesticides of different brands including organochlorines, organophosphates, carbamates, pyrethroids and fumigants were stocked for sale by the retai1ers with herbicides being the most highly demanded (50%), followed by insecticides (31%). Most of the retailers had never attended training on pesticide handling and management and about half claimed to have experienced unusual health feelings since they were into the business. Various symptoms experienced by some of the retailers included feeling dizzy or dazed (33%), severe headache (26%), feeling weak (23%), nausea (20%), restlessness (20%) among others are all indicators of possible poisoning due to exposure to organophosphate pesticides. Findings from this study show that retailers were likely to have been exposed to pesticide mainly through inhalation as a result of continuous exposure to these chemicals in the course of running their businesses. Being an important link in pesticide distribution chain, it is suggested that the existing legislation on pesticide registration in Nigeria should be enforced and regular training of the retailers on pesticide handling and management by chemical companies should also be emphasized and monitored. Regular biological monitoring studies to ascertain the exposure level and possible health effects on the retailers should be given great attention.